2011
DOI: 10.1007/s10552-011-9754-3
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus and increased risk of biliary tract cancer: systematic review and meta-analysis

Abstract: These findings strongly support the link between diabetes and increased risk of cancer of biliary tract and its subsites: gallbladder cancer or extrahepatic cholangiocarcinoma, but not cancer of ampulla of Vater.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
53
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 47 publications
6
53
2
1
Order By: Relevance
“…Particularly, findings on BTC were inconsistent after controlling for obesity [2]. Furthermore, most of the studies accounted for general obesity, but not for abdominal obesity, which we have previously shown to be an independent risk factor for GBC and HCC [9].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Particularly, findings on BTC were inconsistent after controlling for obesity [2]. Furthermore, most of the studies accounted for general obesity, but not for abdominal obesity, which we have previously shown to be an independent risk factor for GBC and HCC [9].…”
Section: Introductionmentioning
confidence: 85%
“…Studies on biliary tract cancer (BTC), including extrahepatic bile duct (EBD) and gallbladder cancer (GBC), have shown inconsistent results regarding diabetes status [2], whereas the evidence for an association between diabetes and hepatocellular carcinoma (HCC) has been more straightforward [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Previous meta-analyses have demonstrated that DM is associated with increased risks of breast, colon and pancreatic cancers (4,10,25,26). Furthermore, a recent German cohort study identified an excess overall cancer risk among diabetic patients, with an odds ratio for all cancers of 1.64 in comparison with the control group (27).…”
Section: Discussionmentioning
confidence: 99%
“…Gallstone is closely in related to GBC risk [41]. Meanwhile, obesity tends to be accompanied with DM, which is also associated with increased GBC risk [6,42]. However, most studies did not adjust for these risk factors.…”
Section: Discussionmentioning
confidence: 99%